2021
DOI: 10.1111/jan.14789
|View full text |Cite
|
Sign up to set email alerts
|

Suicide care from the nursing perspective: A meta‐synthesis of qualitative studies

Abstract: Aims: To explore nurses' experiences of suicide care and to identify and synthesize the most suitable interventions for the care of people with suicidal behaviour from a nursing perspective.Design: Qualitative meta-synthesis. Data sources:Comprehensive search of five electronic databases for qualitative studies published between January 2015 and June 2019. Review methods:The PRISMA statement was used for reporting the different phases of the literature search and the Critical Appraisal Skills Programme (CASP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 45 publications
(152 reference statements)
1
17
0
Order By: Relevance
“…This is evident in the culture of blame that exists in mental health settings surrounding suicide (Wand, 2017). In a meta‐analysis by Clua‐García et al (2021) authors report that some nurses feared that their organization would take legal action and blame them if they were unable to prevent a suicide attempt. Additionally, participants in a qualitative study by Morrisey & Higgins (2019) reported that discussions regarding suicide during their nursing education were based on a preventative risk framework where professional responsibility and accountability was emphasized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is evident in the culture of blame that exists in mental health settings surrounding suicide (Wand, 2017). In a meta‐analysis by Clua‐García et al (2021) authors report that some nurses feared that their organization would take legal action and blame them if they were unable to prevent a suicide attempt. Additionally, participants in a qualitative study by Morrisey & Higgins (2019) reported that discussions regarding suicide during their nursing education were based on a preventative risk framework where professional responsibility and accountability was emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic relationship is established through listening, warmth, a non‐judgmental attitude, and the establishment of a safe environment where suicide can be openly discussed, hope can be promoted, and patient involvement in their own care can be facilitated (Cutcliffe & Barker, 2002; Sun et al, 2006; Clua‐Garcie et al, 2021; Derblom et al, 2021). The therapeutic nurse–patient relationship is valued by nurses as the essential tool for assessing and addressing the needs of people experiencing suicidality (Clua‐Garcie et al, 2021). The quality of this relationship however is significantly influenced by the environment in which it takes place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate pedagogy and student support services must be considered for nursing undergraduate students as the emotional intensity of dealing with suicide prevention is a focal point in preparing and supporting prospective nursing professionals [ 16 , 23 , 28 ]. A review of qualitative studies indicates that it is necessary to improve nurses’ relational skills and monitor the emotional impact related to suicide in order to promote more qualified care [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nursing professionals can play a crucial role in suicide prevention and provide significant insight into the prognosis of people at risk of suicide [ 10 , 11 , 12 , 13 ]. Suicidal behavior is considered an enigmatic phenomenon, and assistance to people with suicidal behavior is considered by nursing professionals as a critical and challenging moment, which evokes feelings varied and requires knowledge, skills, and emotional control [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%